2017
DOI: 10.1501/vetfak_0000002767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season and altitude on biological active certain phenolic compounds levels and partial standardization of propolis

Abstract: Summary: Propolis has antibacterial, antiviral, antifungal, anti-inflammatory, antitumoral, antioxidant, immunomodulatory, tissue regeneration, anti-ulcer, analgesic, local anaesthetic, and antiseptic effects related to its chemical components. The aim of the present study was to determine certain biological active phenolic compounds and their levels in propolis collected from Bursa province, and to evaluate propolis quality and effects of altitude and season. Propolis samples were collected using propolis tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…intensify. Besides, different seasonal effects have also been considered to influence the metabolism of secondary metabolites of plants growing at different altitudes (Oruc et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…intensify. Besides, different seasonal effects have also been considered to influence the metabolism of secondary metabolites of plants growing at different altitudes (Oruc et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction step was carried out as described by Oruç et al. ( 2017 ) with slight modifications. Briefly, 1 g of propolis sample was extracted with 20 mL of 70% EtOH at ambient temperature for 1 h using a multi‐vortex (Multi Reax, Heidolph, Germany), and then the sample was ultrasonicated for 15 min (Wise Clean, DAIHAN Scientific, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…The dried extract was dissolved in 2 mL of absolute methanol and kept at 4°C until used. Appropriate dilutions were made, and the diluted extracts were used for the determination of phenolic compounds by LC–MS/MS and also for the determination of total phenolics (TP) content (Oruç et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…described in Senegalese propolis 58 For BC2, seven compounds were identified belonging to two structural classes of polyphenols, chromone-C-glucoside and prenylflavanone derivatives (8)(9)(10)(11)(12)(13)(14), some of which were described for the first time in propolis (Figure 3). and identified as biflorin (8) and isobiflorin (9), two chromanone-Cglucosides newly described in propolis, previously described in Pancratium biflorum 64 27). The isomer in position 8 was proposed in first position, but comparison with literature data 68,69 showed that it is the isomer in position 6.…”
Section: Chemical Composition Of Bc1 and Bc2mentioning
confidence: 99%
“…The chemical composition of propolis is known to be complex and varies according to plant species growing around the hive, from which bees collect exudates 7 . It is accepted that several factors, such as the floristic composition of the area, the place and time of collection, the season, the type of collector, the availability and altitude, and the food activity developed during the exploitation of the propolis have an impact on the chemical composition of the propolis 8,9 . There are different types of propolis, depending on the geographical area of production, botanical source, and chemical composition.…”
Section: Introductionmentioning
confidence: 99%